PERANAN SATUAN POLISI PAMONG PRAJA (SATPOL-PP) DALAM MENERAPKAN PENGAMANAN DAN KETERTIBAN DI PASAR INPRES KALIANDA KABUPATEN LAMPUNG SELATAN - Jamal Jamal; Eka Suaib; Agusmiar Lispawandi (Universitas Bandar Lampung (UBL), 2020)
The problems in this study are: (1) How the Role of the Civil Service Police Unit in security and control in Kalianda Inpres Market, South Lampung Regency. (2) What aspects are hampering the role of the Civil Service Police Unit in security and control in Kalianda Inpres Market, South Lampung Regency.The method of this research is to use qualitative descriptive research type. The use of this method is to describe the Role of the Civil Service Police Unit in Implementing security and order in the Kalianda Inpres market in South Lampung Regency, assessing qualitatively, how all data is obtained directly from informants in the field using interviews and document studies.The results showed that the Role of the Civil Service Police Unit (Satpol-PP) in Implementing Basic Tasks and Functions in the Kalianda Inpres Market has been going well, the leadership of the South Lampung District Civil Service Police Unit has implemented existing regulations by assigning tasks to employees in accordance background and ability, although in its implementation is not yet optimal, it is due to human resource capability, which is relatively lacking. Then the inhibiting aspects, namely, (1) Employees of the Civil Service Police Unit of South Lampung Regency, do not fully know the exact main tasks and functions. (2) Position of the Civil Service Police Unit (Satpol-PP) of South Lampung Regency as a security, often working is not the main task that should be carried out, so that the employee does not carry out the work optimally. (3) South Lampung Regency Civil Service Police Unit, often has a solid task assigned by the leadership so that overlapping duties and authority often occur by employees in the Civil Service Police Unit of South Lampung Regency .